The Assessment of Physicochemical and Antimicrobial Properties of Hydrophilic Gels Containing Tetracycline Hydrochloride and Various Concentrations of Ethanol - Agnieszka Kostrzębska; Adam Junka; Malwina Brożyna; Witold Musiał (MDPI AG, 2024)
The high prevalence of acne, which affects nearly 85% of adolescents and young adults, underscores the importance of exploring new therapeutic solutions. The aim of the present study was to design a stable hydrogel formulation containing tetracycline hydrochloride (TC) in the presence of ethanol at various concentration levels. The antibiotic stability was assessed over a period of 84 days using the HPLC method. The rheological properties of the formulations and their microbiological activity were also evaluated. Hydrogels without ethanol and those containing 5% and 25% alcohol showed similar rheological properties and high stability of the antibiotic throughout the observation period. The formulation with the highest ethanol content of 50% differed significantly from the others in terms of rheological properties. Although the flow and viscosity curves were like those of the other formulations, the viscosity values were significantly lower. The stability of tetracycline in this formulation was also significantly lower, and by the 84th day of observation, the concentration of the drug had decreased to almost 45% of its initial content. The formulations containing the highest concentration of ethanol displayed the highest activity against the biofilm of the acne-causing agent, Cutibacterium acnes. The study demonstrated the possibility of developing stable and antimicrobial effective hydrogel formulations with tetracycline and ethanol as a substance enhancing drug penetration into the hair follicles.